(untitled) (Research, Society and Development, 2022)
The Maracaju mountain range is known for its environmental diversity and scenic beauty, in addition to the presence of districts that have a rich history, which were isolated due to the precariousness of access to the region. The government, aiming to protect the natural resources of the region, created the Environmental Protection Area Estrada-Parque Piraputanga, which runs along MS 450, passing through the districts of Camisão and Piraputanga, municipality of Aquidauana, Mato Grosso do Sul. 19 years after the creation of the park-road, the road was paved, aiming to boost tourism in the region and improve the income of the residents of the districts. The improved access provided more traffic on the road and the creation of new businesses, offering new economic options to residents and visitors. However, with the advance of new activities, new problems arise, such as solid waste management. Based on this information, the objective was to investigate whether the asphalt paving was accompanied by planning regarding waste management, which tends to increase with the increase in tourism in these districts, located in the Environmental Protection Area of the municipality of Aquidauana. As a result, it is suggested that the trash cans available in the Districts be adequate, as well as the promotion of the distribution of trash cans at tourist sites and visitor awareness, based on an Environmental Education policy.